Clinical diagnostic biomarker “circulating tumor cells” in breast cancer - a meta-analysis - Bai, Shiyan; Lin, Shujin; Lin, Ting; Wang, Qiaowen; Cheng, Cui; Lin, Junru; Zhang, Ying; Jiang, Xiwen; Han, Xiao (Frontiers in Oncology, 2023)
OBJECTIVE：Using meta-analysis, we evaluate circulating tumor cells(CTCs) as a potential diagnostic tool for breast cancer. METHODS：A document search was conducted using publicly available databases up to May 2021. Specific inclusion and exclusion criteria were formulated and summarize relevant data through literature types, research types, case populations, samples, etc. Subgroup analysis of documents based on regions, enrichment methods, and detection methods. The included research projects were evaluated using DeeKs bias, and evaluation indicators such as specificity(SPE), sensitivity(SEN), diagnosis odds ratio (DOR) were used as evaluation indicators. RESULTS: 16 studies on the use of circulating tumor cells to diagnose breast cancer were included in our meta-analysis. Overall sensitivity value was 0.50 (95%CI:0.48-0.52), specificity value was 0.93 (95%CI:0.92- 0.95), DOR value was 33.41 (95%CI:12.47-89.51), and AUC value was 0.8129. CONCLUSION: In meta-regressions and subgroup analysis, potential heterogeneity factors were analyzed, but the source of heterogeneity is still unclear. CTCs, as a novel tumor marker, have a good diagnostic value,but its enrichment and detection methods still need to continue to be developed to improve detection accuracy . Therefore, CTCs can be used as an auxiliary means of early detection, which is helpful to the diagnosis and screening of breast cancer.